Production of diesel fractions by catalytic cracking of vacuum gas oil and its mixture with cottonseed oil under the influence of a magnetic field - Tarana Mammadova; Mutallim Abbasov; Nahid Movsumov; Tarana Latifova; Aynur Hasanova; Zumrud Kocharli; İrada Khalafova; Vaqif Abbasov (Egyptian Journal of Petroleum)
The influence of the 0.4 T magnetic field on catalytic cracking of the vacuum gasoil and its mixture with 5% cottonseed oil was evaluated. Magnetic field intensity excites aromatic resins existing in the vacuum gasoil and causes more effective cracking. Catalytic cracking was conducted using commercial X-zeolite fluid catalytic cracking catalyst and reaction products, especially gasoline and diesel fractions were analyzed in detail. Magnetic field increased the yield of the diesel fraction from 7 to 33% and enriched its composition with aromatic hydrocarbons while opposite effect was observed in gasoline. Cracking mechanisms in formation of gasoline and diesel range hydrocarbons were briefly discussed. Keywords: Magnetic field, Catalytic cracking, Vacuum gasoil, Cottonseed oil, Green gasoline